Rancang Bangun Sistem Keamanan Laboratorium Menggunakan Face Recognition Berbasis IoT - Afiyat, Nur; Ghilmil Mubtadi (Jurnal Studi Multidisiplin Qomaruna, 2024)
The laboratory security system based on the Internet of Things (IoT) is designed to enhance security and surveillance efficiency. This system utilizes the ESP-32 CAM camera to manage access control and real-time room monitoring, with Firebase serving as the facial image database and Telegram as the notification platform. The access control testing with 5 samples demonstrated that the system can recognize user faces with good accuracy, although recognition errors occurred when the distance and viewing angle were not optimal. The average delay in sending notifications via Telegram was 18.528 ms, indicating a fast and real-time response. Additionally, the room monitoring system was able to stream real-time video without significant interruptions, accessible through the laboratory management web interface. Although the monitoring test was limited to real-time functionality, the results showed that the system operated according to the design. This system can be an effective security solution for laboratories, with some improvements needed for optimal performance under non-ideal conditions.